2014
DOI: 10.14202/vetworld.2014.933-937
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of efficiency of sire model and animal model in Holstein Friesian crossbred cattle considering first lactation production and fertility traits

Abstract: Aim: The present investigation was conducted for evaluating the efficacy of estimating breeding values (BVs) using univariate animal model in comparison to sire model. The various parameters considered for evaluating the efficiency of both linear models were coefficient of determination (R 2 ), coefficient of variation (CV), within sire variance or error variance and spearman's rank correlation estimates. Materials and Methods:Data for the present investigation were spread over a period of 34 years from 1978 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…The estimated breeding value of Persistency averaged as -317.30±12.71 in Murrah buffaloes [7]. Lower ranges for FLMY (553.86) and higher ranges for MY/FLL (1.87) and MY/FCI (2.14) in Holstein Friesian crossbred cattle were reported [8]. The higher range of estimated breeding values of sires by BLUP method for MYLL, MYFCI and MYASC as 5.4 to 7.44, 3.13 to 5.49 and 0.86 to 1.31 in Murrah buffaloes compared to the present study [9].…”
Section: Resultsmentioning
confidence: 99%
“…The estimated breeding value of Persistency averaged as -317.30±12.71 in Murrah buffaloes [7]. Lower ranges for FLMY (553.86) and higher ranges for MY/FLL (1.87) and MY/FCI (2.14) in Holstein Friesian crossbred cattle were reported [8]. The higher range of estimated breeding values of sires by BLUP method for MYLL, MYFCI and MYASC as 5.4 to 7.44, 3.13 to 5.49 and 0.86 to 1.31 in Murrah buffaloes compared to the present study [9].…”
Section: Resultsmentioning
confidence: 99%
“…LSQ (23.22%), BLUP-SM (22.89%) and BLUP-AM (21.35%) indicating that all these methods were almost equally stable. Dash et al (2014) also reported the CV (%) as 24.09 and 22.05 for first lactation 305-day milk yield in Holstein Friesian crossbred cows using sire and animal model, respectively.…”
Section: Coefficient Of Variation (Cv)mentioning
confidence: 99%
“…On the other hand, Abou Saq and Ben Naser (2021) obtained a large positive (p<0.0001) PT of + 65.71 kg/ year presenting phenotypic values between 915 and 13845.6 kg/year in Friesian cattle. Also, Dash et al (2016), Konkruea et al (2017) and Vasquez et al (2021) obtained positive trends of +18.71, 21.3 and 294.3 kg/year, respectively, for the milk of Holstein cows and suggested that yield improvement is a result of the applied selection policy emphasizing exclusively the production trait and improvements in management . According to M'hamdi et al (2012), changes in herd size, age of cows, and management practices introduced from one year to another could be responsible for variation in milk production.…”
Section: Phenotypic Trend Of Milk Yieldmentioning
confidence: 94%